Pseudomonas aeruginosa and Staphylococcus aureus communication in biofilm infections: insights through network and database construction - Magalhães, Andreia P. (2019)
AbstractThe polymicrobial nature of most infections is often characterized by complex biofilm communities, where pathogen interactions promote infection progression and severity. Quorum-sensing, the major regulator of virulence and inter-species communication, is a promising target for new anti-infective strategies. This study aimed at collecting and analysing experimental information on the molecular basis of Pseudomonas aeruginosa and Staphylococcus aureus interactions in biofilms. Data were systematically annotated from relevant full-text papers optimally retrieved from PubMed, reconstructed as networks and integrated with specialized databases to identify promising antimicrobial targets. Network analysis revealed key entities regulating P. aeruginosa/S. aureus interactions, for instance the PqsABCDE/PqsR quorum-sensing system, which affects S. aureus growth and biofilm formation. By identifying the most reported P. aeruginosa virulence factors affecting S. aureus, for example, HQNO and siderophores, a list of experimentally validated agents affecting those factors, ranging from synthetic drugs to natural plant extracts, was constructed. The complex experimental data on P. aeruginosa/S. aureus interactions were for the first time systematically organized and made publically available in the new Inter-Species CrossTalk Database (www.ceb.uminho.pt/ISCTD).